Salidroside Stimulates Mitochondrial Biogenesis and Protects against H(2)O(2)-Induced Endothelial Dysfunction - Xing, Shasha (Hindawi Publishing Corporation, 2014)
Salidroside (SAL) is an active component of Rhodiola rosea with documented antioxidative properties. The purpose of this study is to explore the mechanism of the protective effect of SAL on hydrogen peroxide- (H(2)O(2)-) induced endothelial dysfunction. Pretreatment of the human umbilical vein endothelial cells (HUVECs) with SAL significantly reduced the cytotoxicity brought by H(2)O(2). Functional studies on the rat aortas found that SAL rescued the endothelium-dependent relaxation and reduced superoxide anion (O2(∙−)) production induced by H(2)O(2). Meanwhile, SAL pretreatment inhibited H(2)O(2)-induced nitric oxide (NO) production. The underlying mechanisms involve the inhibition of H(2)O(2)-induced activation of endothelial nitric oxide synthase (eNOS), adenosine monophosphate-activated protein kinase (AMPK), and Akt, as well as the redox sensitive transcription factor, NF-kappa B (NF-κB). SAL also increased mitochondrial mass and upregulated the mitochondrial biogenesis factors, peroxisome proliferator-activated receptor gamma-coactivator-1alpha (PGC-1α), and mitochondrial transcription factor A (TFAM) in the endothelial cells. H(2)O(2)-induced mitochondrial dysfunction, as demonstrated by reduced mitochondrial membrane potential (Δψm) and ATP production, was rescued by SAL pretreatment. Taken together, these findings implicate that SAL could protect endothelium against H(2)O(2)-induced injury via promoting mitochondrial biogenesis and function, thus preventing the overactivation of oxidative stress-related downstream signaling pathways.